Effect of Combination Therapy of Oral Famotidine with Mosapride on Intragastric pH and Gastric Emptying in Rats - Hyun Seok Choi; Eui Joong Kim; Min Seob Kim; Ji Yeon Myung; Myeong Hwan Yu; Yong Sung Kim; Moon Young Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims Studies in healthy humans have reported that the addition of mosapride to acid suppressants resulted in higher intragastric pH than acid suppressant administration alone. We investigated the effect of the addition of mosapride to famotidine on the intragastric pH and gastric emptying rate (GER) in rats. Materials and Methods Sixty male Wistar rats were used in this study. Experimental groups were divided into control, famotidine-only, mosapride-only, and famotidine with mosapride (combination). The first experiment was performed in non-stressed rats. Mosapride was administered by oral gavage 1 hour before the meal, and famotidine was administered just before the meal. The rats were provided with food for 30 minutes. The intragastric pH was measured under isoflurane anesthesia, and the GER was measured after harvesting the stomach. In the stress experiment, rats were exposed to 1-hour restraint stress immediately after mosapride administration and subjected to the same process as in the experiment with the non-stressed rats. Results The famotidine-only and combination groups showed significantly higher gastric pH levels than the control group in non-stressed (P<0.01 and P<0.001, respectively) and stressed (P<0.001 and P<0.001, respectively) rats. The combination group also showed significantly higher intragastric pH levels than the famotidine-only group in non-stressed (P<0.01) and stressed (P<0.05) rats. Additionally, combination groups showed a significantly higher GER than the famotidine-only group in non-stressed (P<0.001) and stressed (P<0.01) rats. Conclusions The combination of mosapride with famotidine significantly increased intragastric pH compared to famotidine alone in the non-stressed and stressed rats.